Hybrid war, strategic military surprise and limited war vs military threats from Russia (Economic and Political Thought, 2016)
The article analyses the characteristic features of military threats fromRussia to the northern and eastern flanks of NATO. The starting points arefirst of all the direction and objectives of modernisation and development ofthe Russian military forces, Russian military exercises and possible strategicaims of the expansive policy of Moscow in the Baltic region. Next, the threatis analysed through the prism of three concepts that have appeared in the scientificand public debate in the context of Russia’s aggressive policy: a hybridwar, a strategic military surprise and a limited war. Making conclusions, theauthor states that on no account NATO should treat hybrid operations asa basic scenario of potential aggression by Russia. Such a treat, althoughreal, is neither more probable nor the most dangerous from the point ofview of negative results as well as the possibility of defending against them.The biggest challenge that NATO and such countries as Poland are facing isundertaking steps to protect the eastern flank of the alliance against unexpectedconventional military aggression.